THE PROBLEMS OF COGNITIVE DISSONANCE IN TRANSLATION AND SOLUTIONS TO THEM. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article explores the complexities of cognitive dissonance that translators encounter when interpreting texts across languages and cultures. It delves into how differing cultural contexts and linguistic structures can lead to conflicts between a translator's beliefs and the source material. The article emphasizes the psychological challenges faced by translators and the importance of understanding these dynamics to enhance translation practices.